Hospital safety preparedness during the COVID-19 pandemic: Lessons learned from Vietnam - Thu, Nguyen Thi Hoai; Anh, Bui Thi My; Khanh, Luong Bao; Anh, Pham Tran; Luong, Duong Huy (Frontiers in Tropical Diseases, 2022)
Introduction The rapid spread of SARS-CoV-2, the varying vaccine coverage, and the appearance of new variants posed a significant threat during the pandemic, especially in LMIC countries. Hospitals in Vietnam at both central and local levels have had cross-infection of patients and healthcare workers. Therefore, providing a safe and secure environment for staff and patients was a major focus for all healthcare institutions. Methods We conducted a cross-sectional study, using both quantitative and qualitative methods, to answer the question of how hospital safety during the COVID-19 pandemic in Vietnamese hospitals was implemented and what the challenges were. Secondary data from a recent national survey of safety in 1,398 hospitals conducted by the Vietnam Ministry of Health (MOH) were extracted and analyzed. In-depth interviews of key health managers and health staff in four selected hospitals were performed to further explore challenges in implementing Decision 3088/QD-BYT. Results The proportion of hospitals classified as “safe hospital”, “safe hospital with moderate level”, and “unsafe hospital” was 91.7%, 7.3%, and 1.0%, respectively. The rate of “safe hospital” was highest in the central level hospitals (96.1%), followed by private hospitals (94.4%), provincial hospitals (94.2%), specialized hospitals (93.1%), regional hospitals (93.0%), and district hospitals (89.9%), while “safe hospital” rates were lowest in the ministerial level hospital group (82.2%). Challenges in ensuring hospital safety in public and private hospitals related to COVID-19 transmission, such as lack of preparedness before COVID-19 and other pandemics, limited hospital facility, limited space and equipment, shortage of human resources, inadequate training and knowledge transfer, poor patient compliance in declaring health conditions, and lack of patient understanding of infection prevention methods, were explored. Conclusion Most hospitals in Vietnam successfully met the classification of “safe hospitals” according to Decision 3088/QD-BYT, a key tool for hospitals to self-assess preparedness and responsiveness to the COVID-19 pandemic. The MOH should adapt the criteria in Decision 3088/QD-BYT to be more suitable for the new phase of the pandemic as we move towards “living with COVID”. Furthermore, we recommend that the MOH work to develop mechanisms or regulations that require hospitals to regularly report on disease preparation and responses for future pandemic preparedness.